Efektivitas Bahan Ajar Berbasis Project Based Learning (PjBL) Pada Mata Pelajaran Pendidikan Agama Islam (PAI) - Nadya Azzahra Nadya; Lingga Shevila Wigar Lingga; Idma Firdaus Idma; Muhammad Rifqi Mustofal Fauzi Rifqi; Fiqra Muhamad Nazib Fiqra (Advances In Education Journal, 2025)
This research aims to analyze the literature on Project-Based Learning in PAI subjects. The research used the Systematic Literature Review approach with the following stages determining the theme, searching, selecting literature, analyzing and interpreting, drafting, and dissemination of results. In the research conducted using 20 articles from the selection of 40 articles obtained from various sources with the year of publication 2022-2024 sources with publication years 2022-2024. The focus of the study on 3 things, namely implications, evaluation, and the role of teachers in project-based PAI learning. The results showed that: 1) The implication of project-based learning implications of project-based learning in PAI subjects are considered very effective to improve students' creativity. 2) the results of the evaluation showed that project-based learning is expected to continue. (Project-Based Learning) is expected to be continued considering the positive impact in increasing students' motivation, 3) positive impact in increasing students' motivation, 3) The role of the teacher in the learning process is very important where the teacher must be a facilitator, evaluator, and motivator for students.